2018
DOI: 10.1029/2018gl078007
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Forecasting of Current and Future Circum‐Arctic Ground Temperatures and Active Layer Thickness

Abstract: Mean annual ground temperature (MAGT) and active layer thickness (ALT) are key to understanding the evolution of the ground thermal state across the Arctic under climate change. Here a statistical modeling approach is presented to forecast current and future circum‐Arctic MAGT and ALT in relation to climatic and local environmental factors, at spatial scales unreachable with contemporary transient modeling. After deploying an ensemble of multiple statistical techniques, distance‐blocked cross validation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 65 publications
(107 reference statements)
4
118
1
Order By: Relevance
“…Among the TIR imagers on these satellites, only MODIS provides daily measurements of LST. Numerical modeling studies based on the empirical relationship between the ground temperature and air temperature have taken advantage of the MODIS LST products (e.g., [27][28][29]) to derive static maps of the spatial distribution of permafrost. Recently, a numerical modeling study has combined the MODIS LST products with gridded air temperature data to derive time-series maps of permafrost extent [5].…”
Section: Remote Sensing and Numerical Modeling Studies Of Permafrostmentioning
confidence: 99%
“…Among the TIR imagers on these satellites, only MODIS provides daily measurements of LST. Numerical modeling studies based on the empirical relationship between the ground temperature and air temperature have taken advantage of the MODIS LST products (e.g., [27][28][29]) to derive static maps of the spatial distribution of permafrost. Recently, a numerical modeling study has combined the MODIS LST products with gridded air temperature data to derive time-series maps of permafrost extent [5].…”
Section: Remote Sensing and Numerical Modeling Studies Of Permafrostmentioning
confidence: 99%
“…Mean annual ground temperatures, which impact permafrost distribution, are also changing (Biskaborn et al 2019) in under-sampled regions. Aalto et al (2018b) showed that the highest increases in mean annual ground temperatures by 2080 would occur in Taimyr and east of Taimyr and in a few areas in the Canadian Arctic. Major declines in permafrost extent are expected to occur in the areas surrounding the Taimyr region, northeastern Siberia and in West Greenland (Aalto et al 2018b).…”
Section: High-priority Areas For Terrestrial Environmental Field Resementioning
confidence: 99%
“…Aalto et al (2018b) showed that the highest increases in mean annual ground temperatures by 2080 would occur in Taimyr and east of Taimyr and in a few areas in the Canadian Arctic. Major declines in permafrost extent are expected to occur in the areas surrounding the Taimyr region, northeastern Siberia and in West Greenland (Aalto et al 2018b). Permafrost soils store large SOC stocks that are high in the under-sampled regions in western Canada and some parts of the Canadian archipelago (Hugelius et al 2014, Hengl et al 2017, though permafrost extent is not predicted to decrease in these areas as rapidly as for example in the Taimyr region (Aalto et al 2018b).…”
Section: High-priority Areas For Terrestrial Environmental Field Resementioning
confidence: 99%
See 2 more Smart Citations